Integration of Arabic Language Curriculum in Salaf and Khalaf - Amirul Mukminin; Aisyatul Hanun; Maskuri; Almannah Wassalwa; Dahiru Sani (Alsina : Journal of Arabic Studies, 2025)
This study aims to analyze the design and implementation of an integrated Arabic language curriculum that combines salaf and khalaf pesantren approaches in the Arabic Language Program at Madrasah I’dadiyah Salafiyah Syafi’iyah Sukorejo Situbondo. The integration responds to contemporary challenges in Arabic education that require competence in classical text comprehension alongside communicative language use. Employing a descriptive qualitative approach, data were collected through observation, in-depth interviews, and document analysis involving curriculum documents, teachers, students, and institutional management. The findings indicate that the curriculum integrates grammatical-textual instruction with communicative-oriented practices, as reflected in its structure and pedagogical implementation. Instructional methods include sorogan, bandongan, hiwar, muhadathah, and qirā’ah, which facilitate students’ engagement with both classical texts and active language use. At an indicative level, the integrated curriculum appears to support the development of diverse Arabic language competencies within the pesantren context. This study contributes conceptually and practically to discussions on contextual and sustainable Arabic language curriculum development in Islamic boarding schools.